Penanganan Fisioterapi Kasus Ispa Dengan Intervensi Massage Dan Clapping - Fikma Ainun; Shava Intana Fernando; Anggun Wardani; Dini Nur Alpiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Acute Respiratory Infection (ARI) is a major health issue among children and often leads to secretion accumulation that interferes with breathing. Chest physiotherapy, particularly massage and clapping techniques, is believed to be effective in clearing the airways. This study aims to examine the physiotherapy management of ARI cases using massage and clapping interventions. Methods: This research used a case series design with a qualitative descriptive approach involving three pediatric subjects (S, L, and M), aged 8–30 months, diagnosed with ARI. Physiotherapy interventions were conducted at the Physiotherapy Unit of Fatmawati Central General Hospital, consisting of massage and clapping administered twice daily for five days. Respiratory status was measured through respiratory rate, cough frequency, and degree of dyspnea using the Modified Respiratory Distress Assessment Scale (MRDAS), recorded before and after each session. Data were analyzed descriptively. Results: All three subjects showed improvement in respiratory status after the intervention. The respiratory rate of subject S decreased from an average of 55 breaths/min to 32 breaths/min, subject L from 60 to 36 breaths/min, and subject M from 48 to 29 breaths/min. Cough frequency also significantly decreased: S from 15 times/5 minutes to 2 times/5 minutes, L from 20 to 3 times/5 minutes, and M from 12 to 1 time/5 minutes. Dyspnea scores (MRDAS) in all subjects decreased to 0 (no dyspnea) by the end of the intervention (S from 5 to 0, L from 6 to 0, and M from 4 to 0). Subjective responses from parents also indicated that the children appeared more comfortable and had improved appetite. Conclusion: Physiotherapy management using massage and clapping interventions is effective in improving respiratory status (reducing respiratory rate, cough frequency, and dyspnea severity) in pediatric ARI cases. Personalized interventions play a crucial role in secretion mobilization and accelerating recovery.